Estimasi Jarak Tempuh Order Picking System - Low Level to Part di PT. GMS - Chandra, Agung (Metris: Jurnal Sains dan Teknologi, 2015)
Travel distance has an important role in order picking system, low-level picker-to-part, especially in warehousing productivity. Reducing travel distance means reducing travel time. Research was conducted at PT.GMS that uses random storage which means every item has an equal probability and every item is taken and used by production. Access frequency is assumed to be the same. Travel distance estimation is using probability calculation approach and combination with uniform distribution. Several methods are used to explore the shortest distance: Return Without Repetition, Midpoint Heuristics, and Traversal Without Skip. The results has shown that Midpoint strategy is better than Return Without Repetition and Traversal Without Skip.